Basics of theoretical and methodological evaluation for exercising of Mongolian racehorses - Otgon, Myagmarsuren; Gelegsenge, Gereltsetseg; Tsevegmid, Khaliunaa; Badgar, Khandsuren; Tsogtgerel, Munkhtuul; Chuluunbat, Oyuntsetseg; Erdemsurakh, Ochbayr; Sembe, Oyungerel; Bat, Otgontugs; Chimedtseren , Khorolmaa (Mongolian Journal of Agricultural Sciences, 2022)
The speed at which a racehorse can reach when its heart rate is 200 beats per minute (bpm) is called the V200. Researchers have found that racehorses who performed better at higher levels of V200 were more likely to succeed without injury. Therefore, researchers consider exercise to be the preferred method of assessment of muscle training. The THR100 represents the time it takes for the racehorse’s heart rate to decrease from the V200 and stabilize to 100 bpm at the end of the race. When the racehorse’s muscle cells switch to an aerobic mode at maximal effort, the THR100 stabilizes for a short period of time, though this stabilization can vary by horse breed and race. We examined parameters such as post-exercise V200, THR100, general blood parameters and blood lactate dynamics of Mongolian racehorses during a dressage event. Mongolian horses’ V200 averaged at around 46.2 km/h, and their THR100 averaged at around 11.8 minutes. At the beginning and end of the exercise, hematocrit (5.7%) and granulocytes (11.1%) were increased, whereas lymphocytes (9.7%) decreased. Also, blood lactate concentrations decreased steadily when measured in intervals of 0, 15, and 30 min to 16.2, 10.4, and 4.5 mmol/l, respectively. Mонгол хурдан морины уяа сойлгын үнэлгээний онол, арга зүйн үндэс Хураангуй Хурдан морь ачаалал авснаас хойш зүрхний мөчлөгийн давтамж 200 bpm хүрэх үеийн хурдны үзүүлэлтийг V200 гэнэ. V200 өндөр байх тусам дасгалжилт сайн байх төдийгүй амжилт гаргах магадлал өндөр, бэртэл, гэмтэлгүй уралдааны ачааллыг давдаг болохыг судлаачид тогтоосон. Ачааллын дараа зүрхний мөчлөг буурч 100 bpm-с доошлох хугацаа бөгөөд энэ нь ачааллын үед анаэроб энергийн нөөцөөс хамаарна. Дасгалжилт дээд зэргээр хангагдсан, булчингийн эс аероб дасгалжилтын горимд шилжсэн үед энэхүү үзүүлэлт богино хугацаанд тогтворждог. Бид соёолонгоос дээш насны 16 морины уяа сойлгын явцад V200, THR100, оргил зүрхний мөчлөг, 25 морины гематологийн ерөнхий үзүүлэлт, 8 морины ачааллын дараах цусан дахь сүүний хүчлийн хөдлөл зүйг тус тус тодорхойлов. Туршилтын морьдын V200 дунджаар 46.2 км/ц, оргил зүрхний мөчлөг 234, THR100 дунджаар 11.8 минут байна. Уяа сойлгын төгсгөл үед гематокрит (5.7%↑), нийт мөхлөгт цагаан эсийн эзлэх хувь (11.1%↑) өсөж, лимфоцитийн эзлэх хувь (9.7%↓) буурч байна. Ачааллын дараах цусан дахь сүүний хүчлийн агууламж уяа сойлгын эхэн үед 0 минутад 21.4, 15 дахь минутад 17.5, 30 дахь минутад 12.7 ммоль/л байх ба энэхүү зүй тогтлоор уяа сойлгын төгсгөлд 16.2, 10.4, 4.5 ммоль/л болж ачааллын дараа 0 минут дахь агууламж буурахын зэрэгцээ бууралтын эрчим нэмэгдэх зүй тогтол ажиглагдав. Түлхүүр үг: V200, THR100, зүрхний мөчлөг, хурдан морь, сүүний хүчил